2017
DOI: 10.1186/s13550-017-0288-x
|View full text |Cite
|
Sign up to set email alerts
|

First in-human radiation dosimetry of 68Ga-NODAGA-RGDyK

Abstract: BackgroundIntegrin-targeting radiopharmaceuticals have potential broad applications, spanning from cancer theranostics to cardiovascular diseases. We have previously reported preclinical dosimetry results of 68Ga-NODAGA-RGDyK in mice. This study presents the first human dosimetry of 68Ga-NODAGA-RGDyK in the five consecutive patients included in a clinical imaging protocol of carotid atherosclerotic plaques. Five male patients underwent whole-body time-of-flight (TOF) PET/CT scans 10, 60 and 120 min after trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
1
24
1
Order By: Relevance
“…3). Estimated TIAC for the choroid plexuses with 18 F-AzaFol (4.62E− 04 MBq h/MBq) is higher than TIAC previously reported in [20] where a 68 Ga-RGD compound was used (3.08E− 04 MBq h/MBq). Nevertheless, when considering the same organ mass and geometry (with OLINDA sphere model and a mass of 2.76 g) used for the AD calculation, the AD estimate to the choroid plexuses for the 18 F-Aza-Fol (2.47E− 02 μGy/MBq) was lower than the dose estimated of the 68 Ga-RGD compound (3.96E− 02 μGy/MBq).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…3). Estimated TIAC for the choroid plexuses with 18 F-AzaFol (4.62E− 04 MBq h/MBq) is higher than TIAC previously reported in [20] where a 68 Ga-RGD compound was used (3.08E− 04 MBq h/MBq). Nevertheless, when considering the same organ mass and geometry (with OLINDA sphere model and a mass of 2.76 g) used for the AD calculation, the AD estimate to the choroid plexuses for the 18 F-Aza-Fol (2.47E− 02 μGy/MBq) was lower than the dose estimated of the 68 Ga-RGD compound (3.96E− 02 μGy/MBq).…”
Section: Discussioncontrasting
confidence: 58%
“…For the choroids, we also applied a more realistic AD estimation using the Monte Carlo-derived analytical approach proposed by Amato et al [19] in which the complex geometry of this organ was approximated using a set of simple geometrical structures such as (cylinders and parallelepipeds). The mass of the choroids was estimated to be 2.76 g and 1.81 g for male and female as previously reported in [20].…”
Section: Absorbed Dose (Ad) Estimationsmentioning
confidence: 63%
“…As previously described, quantitative accuracy for 68 Ga PET/CT was assessed to be within 6% of the expected value [20].…”
Section: Methodsmentioning
confidence: 99%
“…68 Ga-NODAGA-RGD can be produced locally in centers with access to a 68 Ga generator [15] and radiolabeling can be easily done in kit-based or automated modules. It targets the α v β 3 integrins [8][9][10], and showed promising results in animal trials and demonstrated safe dosimetry profile [16][17][18]. Patients with different tumor types have also been reported using 68 Ga-NODAGA-RGD [16,19,20], but no specific study has been performed in a HNSCC population.…”
Section: Introductionmentioning
confidence: 99%